The relationships between numeracy scores and soft skills in employed and unemployed Americans. Issue 2 (20th June 2020) - Sulak, Tracey N.; Wilson, Robin; Renbarger, Rachel L.; Kaul, Corina R.; O'Guinn, Nicole
Abstract: Over the past two decades, the skills needed to be successful in the workplace have expanded beyond technical skills to include 21 st ‐century soft skills such as critical thinking, communication, collaboration, and creativity. A structural equation model of the ATC21S TM was used to investigate the relationship between 21 st ‐century soft skills and numeracy for employed and non‐employed Americans ( N = 3, 948) included in the Program for the International Assessment of Adult Competencies (PIAAC) data. Higher numeracy scores predicted employment while 21 st ‐century soft skills did not. The results of this study may indicate a greater need to focus on numeracy in compulsory education as well as adult basic education.